THE CHALLENGE OF REGULATORY COHERENCE IN THE BRAZILIAN ENERGY TRANSITION: AN ANALYSIS OF THE BIOFUELS REGULATORY FRAMEWORK IN LIGHT OF THE PARIS AGREEMENT - Starling, Eliseu Teixeira; Squeff, Tatiana de Almeida F. R. C.; Frade, Gabriel Silva (Seven Editora, 2025)
This article analyzes the evolution of the regulatory framework for biofuels in Brazil, focusing on its alignment with the commitments of the Paris Agreement and the challenges of the energy transition. Based on a documentary and bibliographical analysis, it investigates the systemic coherence and normative hierarchy of biofuel legislation in relation to the Brazilian legal-environmental framework. The results point to the need for regulatory reform that promotes the sustainability and decarbonization of the sector, overcoming dependence on fossil fuels and encouraging the bioeconomy.DOI: https://doi.org/10.56238/sevened2025.040-012